Estudio del impacto económico causado por el COVID-19 en el cantón urbano de Otavalo - Imbabura en 2020. - Moposita, Jorge N. (2021)
The COVID-19 pandemic is one of the most serious challenges humanity has faced. The world is witnessing an economic collapse that will severely impact the well-being of the population. In the Otavalo economy, COVID-19 has caused abrupt changes to each economic sector, seriously affecting Tourism and Commerce, hence the initiative of this research that addressed the study of the economic impact caused by COVID-19 in the urban canton of Otavalo - Imbabura in 2020, the methodology used in this research was developed by a quantitative and qualitative approach because information was collected through a survey applied to 374 taxpayers registered in the SRI.